2020
DOI: 10.3389/fpls.2020.591457
|View full text |Cite
|
Sign up to set email alerts
|

Gene Pyramiding for Achieving Enhanced Resistance to Bacterial Blight, Blast, and Sheath Blight Diseases in Rice

Abstract: Bacterial blight, blast, and sheath blight are the commonest diseases causing substantial yield loss in rice around the world. Stacking of broad-spectrum resistance genes/QTLs into popular cultivars is becoming a major objective of any disease resistance breeding program. The varieties ASD 16 and ADT 43 are the two popular, high yielding, and widely grown rice cultivars of South India, which are susceptible to bacterial blight (BB), blast, and sheath blight diseases. The present study was carried out to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 38 publications
5
45
0
Order By: Relevance
“…RPG recovery in the two crosses in the present study did not differ from several earlier wheat breeding programmes where MABB was used for introgression of genes/QTL for biotic and abiotic stresses in wheat (Yadav et al 2015;Mallick et al 2015;Vishwakarma et al 2016;Rai et al 2018;Randhawa et al 2019;Todkar et al 2020: Gautam et al 2020a). This con rmed the utility of MABB for effective introgression of genes/QTL into the agronomically superior genotypes associated with recovery of recurrent parent genome in a relatively short time as also reported earlier in wheat (Mallick et al 2015), rice (Divya et al 2015;Ellur et al 2016;Ramalingam et al 2020;Jamaloddin et al 2020), and maize (Sureshkumar et al 2014;Kaur R et al 2020).…”
Section: Resultssupporting
confidence: 82%
“…RPG recovery in the two crosses in the present study did not differ from several earlier wheat breeding programmes where MABB was used for introgression of genes/QTL for biotic and abiotic stresses in wheat (Yadav et al 2015;Mallick et al 2015;Vishwakarma et al 2016;Rai et al 2018;Randhawa et al 2019;Todkar et al 2020: Gautam et al 2020a). This con rmed the utility of MABB for effective introgression of genes/QTL into the agronomically superior genotypes associated with recovery of recurrent parent genome in a relatively short time as also reported earlier in wheat (Mallick et al 2015), rice (Divya et al 2015;Ellur et al 2016;Ramalingam et al 2020;Jamaloddin et al 2020), and maize (Sureshkumar et al 2014;Kaur R et al 2020).…”
Section: Resultssupporting
confidence: 82%
“…MAS is a well developed method to stack multiple genes, and pyramiding of Pi genes based on this technology has been used in both indica and japonica rice in various breeding programs (Fukuoka et al 2015 ; Orasen et al 2020 ; Xiao et al 2020 ). Combination of Pi genes even with other R genes to bacterial blight, and sheath blight has been achieved in resistance to multiple diseases (Ramalingam et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Marker-assisted gene pyramiding of resistance QTLs have been successfully applied in several crops consequently producing a number of varieties and lines with improved resistances against biotic stresses, such as late blight, bacterial blight, gall midge, mosaic viruses, powdery mildew and many abiotic stresses, such as salinity, drought, heat, and cold with a higher yield and desired nutritional quality (reviewed by Dormatey et al, 2020 ). Especially, the multi-loci polymerization resistance breeding is a success story in rice where plant scientists successfully utilized this technique to accomplish durable resistance against various diseases such as gall midge ( Das and Rao, 2015 ), blast ( Jamaloddin et al, 2020 ), brown planthopper ( Liu et al, 2016 ), bacterial blight ( Singh et al, 2001 ; Joseph et al, 2004 ; Jamaloddin et al, 2020 ; Ramalingam et al, 2020 ), sheath blight ( Ramalingam et al, 2020 ), blast and bacterial blight ( Narayanan et al, 2002 ), bacterial, sheath blight and stem borer ( Datta et al, 2002 ) etc. Wu et al (2019) identified 37 SNP polymerization regions for 36 agronomic traits in 287 pepper accessions which could be the focus of molecular marker development to improve the efficiency of multi-trait pyramid breeding.…”
Section: Downy Mildewmentioning
confidence: 99%